Use of multi-temporal satellite images to characterize the use and occupation of land in the municipality of São Borja -RS - Schiavo, Bruna Nascimento de Vasconcellos; Terra, Lueni Gonçalves; Duarte, Manoela Mendes; Gatiboni, Thales Nascimento (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The disordered growing of cities made indispensable the need to develop efficient policies of environmental planning. To so, studies that aim the understanding of the dynamic of this occupations in different areas are necessary. Before that, this paperwork has the objective to measure the temporal dynamic of the use and occupation of the land in São Borja – RS. Thematic maps of the years 2000, 2005 and 2010 have been elaborated. The results indicate that the class defined as 'field' presented the greatest reduction in the assessed period: from 51,97% of the total mapped area in 2000 to 23,42% in 2010. The class 'exposed soil and urbanization' was the one which showed the greatest growing: from 6,1% in 2000 to 22,63%. The class 'forest' obtained the same behavior, thought in a less significantly: from 16,05% in the first analyzed year to 24,53% in 2010. The class called 'agriculture' showed a very variable behavior during the studied period: in the year 2000 it presented 9,27%, in the year 2005 the mapping indicated 25,14% and in the last year, the percentage dropped to 14,57%. The class of 'water resources' maintained a very similar percentage in all three mapped year (16,61%, 16,69% e 14,85% consecutively). We can conclude that this study can become a very useful and important tool to define and promote the actions of environmental and territorial planning of the public sphere.